Analysis of health care practices in student assistance at the Federal University of Maranhão – Campus Bacanga - NAKASU, Cedric Tempel (2021)
The present study focused on the investigation of health care practices in student assistance at the Federal University of Maranhão (UFMA), Campus Bacanga. The inductive method of research was used, of mixed nature, with a predominance of qualitative analysis, focusing on Brazilian public policies that refer to student assistance in the Federal Institutes of Higher Education (IFES) and their practices at UFMA, aiming to understand how they are performed and to verify the perception of these actions by the students of the institution's on-site undergraduate courses. Data collection was carried out by bibliographic and documentary research, in addition to the application of an online questionnaire-type survey through the Google Forms platform. For data analysis, IRAMUTEQ software was used, in addition to Google Forms itself. We sought to contribute to the scientific knowledge that comprises the theme of health care practices of undergraduate students at Ifes, especially at UFMA - Campus Bacanga, highlighting institutional policies, challenges, achievements and possibilities for future practices, encouraging researchers , community and students for better conditions of access to health policies that enable the construction of a preventive-educational model that favors the autonomy of the subjects involved and society in general. The results show the need to further promote the discussion about public policies aimed at student assistance at the national level, especially health care, and the practices currently carried out at UFMA, in this sense, serve as a model for the PNAES.